Overcoming water scarcity and quality constraints: Dams and Water Storage - Bird, Jeremy; Wallace, Pamela (International Food Policy Research Institute, 2001)
Dams are at the center of many controversies related to the management of water resources and proposals to relieve water scarcity. Two strategic contributions to the Second World Water Forum held in The Hague in March 2000 provide insight.